2013
DOI: 10.1093/jac/dkt107
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antimicrobial activity of ceftaroline against Clostridium difficile and propensity to induce C. difficile infection in an in vitro human gut model

Abstract: Ceftaroline, like ceftriaxone, can induce simulated C. difficile infection in a human gut model. However, low in vivo gut concentrations of ceftaroline and increased activity against C. difficile in comparison with ceftriaxone mean that the true propensity of this novel cephalosporin to induce C. difficile infection remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…Using PolyFermS models, we showed that CD vegetative cells or spores only colonize in TDC reactors after a time period of 7–10 days. Our data are in agreement with previous studies that reported an absence of CD colonization added as spores in the proximal colon section of a three stage colonic fermentation model [29, 30], which may be explained by pH inhibition effect [31]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Using PolyFermS models, we showed that CD vegetative cells or spores only colonize in TDC reactors after a time period of 7–10 days. Our data are in agreement with previous studies that reported an absence of CD colonization added as spores in the proximal colon section of a three stage colonic fermentation model [29, 30], which may be explained by pH inhibition effect [31]. …”
Section: Discussionsupporting
confidence: 93%
“…This result suggests that either the spores were washed out of the system, or that they were able to grow, but remained below the detection limit of the qPCR method (4.4 GC mL −1 ). A quiescent state of CD spores for a period of at least 7 days was previously reported in a three-stage model, and was tentatively explained by the absence of antibiotic treatment [29, 30]. Our data demonstrate that application of antibiotic may not be required for CD spore germination and colonization of an in vitro continuous colonic fermentation model mimicking TDC conditions of an elderly microbiota.…”
Section: Discussionsupporting
confidence: 80%
“…In general, cephalosporins have poor in vitro activity against C. difficile (Table 4). 4052 These studies also showed that Gram-negative anaerobic bacteria, such as Bacteroides spp., which make up a substantial proportion of the gastrointestinal microbiota, typically had low susceptibility to cephalosporins. Ceftaroline and ceftobiprole showed the greatest activity against C. difficile isolates, with an MIC 50 of 2–4 mg/L for both agents; 40,41,52 one review also reported good activity of cefprozil.…”
Section: Are All Cephalosporins the Same With Regard To CDI Risk?mentioning
confidence: 94%
“…4052 These studies also showed that Gram-negative anaerobic bacteria, such as Bacteroides spp., which make up a substantial proportion of the gastrointestinal microbiota, typically had low susceptibility to cephalosporins. Ceftaroline and ceftobiprole showed the greatest activity against C. difficile isolates, with an MIC 50 of 2–4 mg/L for both agents; 40,41,52 one review also reported good activity of cefprozil. 42 As noted earlier, however, most cephalosporins are excreted primarily by the kidney, and thus antimicrobial activity against C. difficile may be of limited clinical relevance for drugs that do not penetrate the gut at therapeutic levels (Table 3).…”
Section: Are All Cephalosporins the Same With Regard To CDI Risk?mentioning
confidence: 94%
“…difficile infection has been described in patients receiving ceftaroline (Lin et al, 2013). Although the effect of the drug on the human gut flora was shown to be minimal (Panagiotidis et al, 2010), ceftaroline like other cephalosporins can induce simulated C. difficile infection in a human gut model (Baines et al, 2013). In addition, ceftaroline was thought to be responsible for an alteration of coagulation in one patient receiving warfarin (Bohm &Crosby, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%